Pendampingan Penerapan Sistim Informasi Akuntansi Melalui Pararel Connected User pada UMKM - Nanang Shonhadji; Diah Ekaningtias; Nadjib Usman (CAPACITAREA : Jurnal Pengabdian kepada Masyarakat, 2022)
ABSTRACT Trading business competition in the City of Surabaya is very competitive, therefore, the best service for customers by providing accurate and fast information needed by customers and suppliers. Partners need the application of a sales accounting information system that uses a parallel-connected user in the reporting of financial statements. The partner in this community service is UD Rino who is engaged in the trade sector. The purpose of this community service is to provide training and assistance in the use of sales information systems, so that the resulting financial reports can be used as information for accurate and fast business decision makers. The results of community service information that partners have successfully operated the sales information system installed on computers in their trading businesses. The results also inform that partners can manage financial information and use it as information for business decision-making. The training and mentoring have been successfully carried out by involving the community service team and partners. The basic contribution to the target audience is the existence of tools that can facilitate partner in managing their finance statement more systematically with the Parallel Connect User approach. In addition, this information system is a medium for the formation of new entrepreneurs who can manage business finances properly and correctly.